Identification Of Aquatic Plant Types (Macrophyta) In Peat Swamp Ecosystems In Pelalawan Village, Pelalawan Regency, Riau Province - Shofiyah Tika Ashilah; Ridwan Manda Putra; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Peat Swamp Ecosystem is one of the ecosystems in the wetlands, which is experiencing a shift in the function of oil palm plantations and Industrial Plantation Forests (HTI). This study aims to determine the types of aquatic plants that live in the Peat Swamp Ecosystem Pelalawan Village, Pelalawan Regency, Riau Province. The method used is the method of observation, with descriptive analysis. Sampling is carried out every day for one week until no new species are found. Samples of aquatic plants were identified by Steenis (1981). The results found that there were 4 classes, 10 families and 10 species of aquatic plants that live in the peat swamp ecosystem. Water growth consists of 2 patterns of life, namely floating type, and emergent type. There are aquatic plant species in the peat swamp ecosystem are Eicchorniacrassipes, Ipomoea aquatica, Salvinianatans, Pistiastratiotes, Lycopodiumclavatum, Echinodoruspalaefolius, Paspalumcommersoni, Cyperusrotundus, Nymphaestellata, andLimnocharisflavaKeyword: Peat Swamp Ecosystem, identification, aquatic plants